Crystal structure of Pseudomonas aeruginosa catabolic ornithine transcarbamoylase at 3.0-A resolution: a different oligomeric organization in the transcarbamoylase family. - Villeret, V (1995)
The crystal structure of the Glu-105-->Gly mutant of catabolic ornithine transcarbamoylase (OTCase; carbamoyl phosphate + L-ornithine = orthophosphate + L-citrulline, EC 2.1.3.3) from Pseudomonas aeruginosa has been determined at 3.0-A resolution. This mutant is blocked in the active R (relaxed) state. The structure was solved by the molecular replacement method, starting from a crude molecular model built from a trimer of the catalytic subunit of another transcarbamoylase, the extensively studied aspartate transcarbamoylase (ATCase) from Escherichia coli. This model was used to generate initial low-resolution phases at 8-A resolution, which were extended to 3-A by noncrystallographic symmetry averaging. Four phase extensions were required to obtain an electron density map of very high quality from which the final model was built. The structure, including 4020 residues, has been refined to 3-A, and the current crystallographic R value is 0.216. No solvent molecules have been added to the model. The catabolic OTCase is a dodecamer composed of four trimers organized in a tetrahedral manner. Each monomer is composed of two domains. The carbamoyl phosphate binding domain shows a strong structural homology with the equivalent ATCase part. In contrast, the other domain, mainly implicated in the binding of the second substrate (ornithine for OTCase and aspartate for ATCase) is poorly conserved. The quaternary structures of these two allosteric transcarbamoylases are quite divergent: the E. coli ATCase has pseudo-32 point-group symmetry, with six catalytic and six regulatory chains; the catabolic OTCase has 23 point-group symmetry and only catalytic chains. However, both enzymes display homotropic and heterotropic cooperativity.